The Role of Anthocyanin Substances from Dragon Fruit Skin Extract in Formalin Content Testing in White Tofu - Endang Sulistyorini; Kirana Nugrahayu Lizansari; Kholilah Febriyanti (SEAS (Sustainable Environment Agricultural Science), 2022)
One of the high-quality processed vegetable food ingredients is tofu. Tofu is made from processed soy milk with a thick texture and molded according to the right nutritional amount. White tofu is the most popular of the various forms of tofu available. Today, tofu producers have taken manipulative actions to anticipate production losses by including preservatives in the mix of ingredients used to make tofu. Most of the tofu production centers provide additional ingredients in the form of preservatives such as formalin to reduce losses from damage to the tofu they produce. The presence or absence of formalin in food can be detected using a unique component found in dragon fruit peel called anthocyanins. The methodology applied in this research is a simple and direct one, with primary data collected in the form of testing samples of white tofu collected from numerous traditional markets in the Banten area (up to ten samples). The aim of the research is to identify formalin in white tofu discovered in numerous traditional markets in Banten using natural component extracts, including dragon fruit peel extract. The results stated that there were two positive samples containing formalin and eight negative samples; the presence of formalin in tofu was indicated by a red color on the tissue. Sellers or customers can detect formalin simply by utilizing dragon fruit, allowing them to avoid formin which is harmful to health, with a simple and low-cost method.